Anais Do Enemet - Encontro Nacional De Estudantes De Engenharia Metalúrgica, De Materiais E De Minas 2017
DOI: 10.5151/1516-392x-26393
|View full text |Cite
|
Sign up to set email alerts
|

MICROESTRUTURA, MICRODUREZA E PARÂMETROS TÉRMICOS DA LIGA DE SOLDA Sn-40%Bi-2%Ag

Abstract: ResumoEsta proposta objetivou desenvolver uma análise teórico/experimental da influência de 2% Ag (em peso) em uma liga de solda Sn-40%Bi solidificada unidirecionalmente em regime transitório de fluxo de calor. Correlações experimentais entre os parâmetros térmicos de solidificação como velocidade de deslocamento da isoterma liquidus -V L , taxa de resfriamento -Ṫ L e parâmetros microestruturais como espaçamentos dendríticos secundários -λ 2 foram determinados. A caracterização microestrutural foi realizada po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The value of the exponent of the equation relating λ1 and V L was different from -1,1 proposed by Bouchard and Kirkaldy 15 for binary alloys. Some authors 20,21,22 have also found different values of exponent for V L in ternary alloys. It is also observed that, for the 5Cu alloy, the values of V L are lower than for the 2Cu alloy, demonstrating the influence of copper on the microstructure.…”
Section: Resultsmentioning
confidence: 99%
“…The value of the exponent of the equation relating λ1 and V L was different from -1,1 proposed by Bouchard and Kirkaldy 15 for binary alloys. Some authors 20,21,22 have also found different values of exponent for V L in ternary alloys. It is also observed that, for the 5Cu alloy, the values of V L are lower than for the 2Cu alloy, demonstrating the influence of copper on the microstructure.…”
Section: Resultsmentioning
confidence: 99%